STRATEGI PEMBENTUKAN KARAKTER MELALUI METODE DONGENG DAN PENDAMPINGAN ANAK DI RUMAH DONGENG KINCIRIA - Arin Wahyuni; Triyanto Triyanto; Widya Noventari (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Abstract: This study aims to describe: (1) General description of the Rumah Dongeng Kinciria. (2) Storytelling strategies at the Rumah Dongeng Kinciria. (3) Implementation of child assistance programs by the Rumah Dongeng Kinciria. The study uses qualitative methods. Data collection uses interviews and documentation. The informants consisted of three people, they were the community founder, curriculum division and public relations division. Data validity testing uses source triangulation and technique triangulation. Data analysis uses an interactive model consisting of data reduction, data presentation, and conclusions. The results of the study show that (1) Rumah Dongeng Kinciria is a social community engaged in the field of character education in the informal education path. (2) Storytelling strategies implemented by the Rumah Dongeng Kinciria are based on catharsis methods supported by attractive media such as dolls and guitars. (3) The implementation of mentoring for children is carried out with storytelling, artwork, and watching educational films based on catharsis methods.